Impact of cAMP on the T-cell response to type II collagen. - Ozegbe, P; Foey, A; Ahmed, S; Williams, R (2004)
There is considerable interest in the possible use of cAMP-elevating agents in the treatment of autoimmune diseases such as rheumatoid arthritis. The objective of this study was to evaluate the impact of different cAMP-elevating agents on the T-cell response to type II collagen within the context of collagen-induced arthritis, a murine model of rheumatoid arthritis. Spleen cells or lymph node cells from type-II-collagen-immunized DBA/1 mice were cultured in the presence of type II collagen plus one of five different cAMP-elevating agents: rolipram, forskolin, prostaglandin E2, 8-bromo-cAMP, or cholera toxin. Levels of interferon-gamma (IFN-gamma), interleukin-4 (IL-4) and IL-5 were measured in culture supernatants by enzyme-linked immunosorbent assay. All of the cAMP-elevating agents tested were found to profoundly suppress IFN-gamma production in a dose-dependent manner. IL-4 and IL-5 production was slightly up-regulated at low concentrations of the cAMP-elevating agents and was modestly suppressed at the highest concentrations of cAMP-elevating agents. Experiments were then carried out to determine whether T cells were directly affected by cAMP-elevating agents or whether the immunomodulatory effects were mediated via antigen-presenting cells. Pulsing T cells alone for a brief period with cholera toxin produced an almost identical effect to pulsing antigen-presenting cells alone, i.e. down-regulation of proliferation, down-regulation of IFN-gamma production with little effect on IL-5 production. It was concluded that cAMP-elevating agents suppressed T helper type 1 responses to type II collagen to a greater extent than T helper type 2 responses. The cAMP-elevating agents could directly influence the activity of T cells but, in addition, influenced the ability of antigen-presenting cells to support T helper type 1 responses.